Effects of melatonin on DNA damage induced by cyclophosphamide in rats - Ferreira,S.G. (2013)
The antioxidant and free radical scavenger properties of melatonin have been well described in the literature. In this study, our objective was to determine the protective effect of the pineal gland hormone against the DNA damage induced by cyclophosphamide (CP), an anti-tumor agent that is widely applied in clinical practice. DNA damage was induced in rats by a single intraperitoneal injection of CP (20 or 50 mg/kg). Animals received melatonin during the dark period for 15 days (1 mg/kg in the drinking water). Rat bone marrow cells were used for the determination of chromosomal aberrations and of formamidopyrimidine DNA glycosylase enzyme (Fpg)-sensitive sites by the comet technique and ofXpf mRNA expression by qRT-PCR. The number (mean ± SE) of chromosomal aberrations in pinealectomized (PINX) animals treated with melatonin and CP (2.50 ± 0.50/100 cells) was lower than that obtained for PINX animals injected with CP (12 ± 1.8/100 cells), thus showing a reduction of 85.8% in the number of chromosomal aberrations. This melatonin-mediated protection was also observed when oxidative lesions were analyzed by the Fpg-sensitive assay, both 24 and 48 h after CP administration. The expression of Xpf mRNA, which is involved in the DNA nucleotide excision repair machinery, was up-regulated by melatonin. The results indicate that melatonin is able to protect bone marrow cells by completely blocking CP-induced chromosome aberrations. Therefore, melatonin administration could be an alternative and effective treatment during chemotherapy.